2010
DOI: 10.1186/1471-2431-10-45
|View full text |Cite
|
Sign up to set email alerts
|

The state of pediatric asthma in Chicago's Humboldt Park: a community-based study in two local elementary schools

Abstract: BackgroundPediatric asthma is a serious public health problem in Chicago and has been designated a high priority concern by residents of Chicago's Humboldt Park, a diverse community area with a large number of Puerto Rican, African American, and Mexican American families.MethodsIn May 2009, following the principles of community-based participatory research, a cross-sectional asthma screening survey was administered to adult caregivers of children attending two Humboldt Park elementary schools. Data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…In Chicago, racial and socioeconomic disparities in pediatric asthma are well documented, with Hispanic and black children from disadvantaged households disproportionately affected. 5,[26][27][28][29][30][31][32] Additionally, it is unclear whether socioeconomic and racial variability in food allergy is intrinsic to the disease verification process; however, many have speculated that it is attributable, in least at part, to barriers to care among racial/ ethnic minorities and disadvantaged households. [33][34][35][36][37] Additionally, this study determined that students attending school on the city' s North-Northwest Side were significantly more likely to have a school health management plan on file than students from any other region of Chicago.…”
Section: Discussionmentioning
confidence: 99%
“…In Chicago, racial and socioeconomic disparities in pediatric asthma are well documented, with Hispanic and black children from disadvantaged households disproportionately affected. 5,[26][27][28][29][30][31][32] Additionally, it is unclear whether socioeconomic and racial variability in food allergy is intrinsic to the disease verification process; however, many have speculated that it is attributable, in least at part, to barriers to care among racial/ ethnic minorities and disadvantaged households. [33][34][35][36][37] Additionally, this study determined that students attending school on the city' s North-Northwest Side were significantly more likely to have a school health management plan on file than students from any other region of Chicago.…”
Section: Discussionmentioning
confidence: 99%
“…The need to carefully define such factors is particularly salient to characterizing stressors effectively within diverse socio-cultural, geographic and ecological settings. Mixed-methods approaches utilized to examine, document and define the relationship and mechanistic and contextual pathways upon asthma morbidity can complement the growing body of population-based research and inform population-based studies guided by community priorities [36,44]. Federal guidelines to address chronic disparities in health [45], as well as results from community-based asthma studies, suggest that engaged research approaches, such as community-based participatory research (CBPR) contribute positively to the enhancement of community capacity to address important contextual triggers, reduce environmental hazards and improve the health of community residents [44].…”
Section: Community Levelmentioning
confidence: 99%
“…Federal guidelines to address chronic disparities in health [45], as well as results from community-based asthma studies, suggest that engaged research approaches, such as community-based participatory research (CBPR) contribute positively to the enhancement of community capacity to address important contextual triggers, reduce environmental hazards and improve the health of community residents [44]. CBPR provides an approach and framework for practitioners, community members and academics to address disparities in health and work in partnership to design, conduct and implement research and to disseminate the findings within affected communities [36,44,46]. …”
Section: Community Levelmentioning
confidence: 99%
“…Screening and disease control data for children in asthma hot spots are also available. Gupta et al (39) found after screening 494 children in low-income elementary schools in Chicago that 25% had diagnosed or probable asthma and that, among those children with a diagnosis, 60% had poorly controlled disease. Nicholas et al (68) found that among 1982 children screened in the Harlem neighborhood of New York City, 29% had been told by a physician that they had asthma.…”
Section: Prevalence and Burden Of Asthmamentioning
confidence: 99%